Aménagement durable des territoires : quel apport d’un outil multimédia d’aide à la délibération ? - Aurèlie Chamaret; Victoria Reichel; Martin O’Connor (Netcom)
Deliberative decision-making approaches are being increasingly favoured for regional development as they assist in overcoming difficulties associated with complexity and uncertainty. This article examines the role of multimedia tools in the decision-making process. An example of the tools we employ is the KerBabel Deliberation Support Tools (KerDST), which is a computer-based tool accessible to all stakeholders. It aims to understand points of convergence and difference and to aid in the choice of future development paths as it represents any problem that involves social choice (e.g. environmental conflicts) through three key dimensions: actors, scenarios, and issues. We discuss two cases in which KerDST has been applied (water management issues in residential development in the UK and urban mobility options in France). Its success as a deliberation tool has allowed us to draw overall lessons about the relevance of such tools in addressing regional sustainable development issues, both in terms of process and design.